Châteaux et maisons fortes en Lorraine centrale - Giuliato, Gérard (Documents d'archéologie française, 1992)
An exhaustive inventory of fortified residences is compared here to written evidence, figurative representations and fieldwork. It retraces the evolution of seigneurial residences of the Xth to XVth centuries. These elements are reinsered into the domaine and social context thanks to the drawing up of unpublished genealogies. In this imposing work a continual contact is maintained between past and present outlining the progress of archaeological research. Actual problems such as the protection of this threatened heritage are also evoked here.